Present state and the perspectives of the ageing of European population. - Długosz, Zbigniew (Bulletin of Geography. Socio-economic Series, 2007)
This paper aims at presenting the process of population ageing in the countries of Europe during the decade 1996-2005, as well as in the perspective till the year 2015, considered against the backdrop of the main factors shaping this process, i.e. the life span, level of fecundity and the percentage of population in the 0-14-year age class, as well as the migration seen in the balance of this process. In further parts of the paper an attempt was made, on the one hand, to point out, the areas of high levels of demographic senility and, on the other hand to underscore the dynamics of the process and thence to indicate the countries most threaten by this phenomenon.